SYNTHESIS, ANTICONVULSANT AND NEUROTOXICITY SCREENING OF SOME NOVEL 2, 5-DISUBSTITUTED - 1, 3, 4 – OXADIAZOLE DERIVATIVES (International Journal of Pharmaceutical Sciences and Drug Research, 2017)
A series of 2, 5-disubstituted - 1, 3, 4 – oxadiazoles (4a-o) were synthesized on refluxing hydrazine carbothioamides with iodine and potassium iodide in ethanolic sodium hydroxide solution starting from methyl-3-amino-4-hydroxy benzoate via synthesis of an intermediate methyl-2-substitutedaryl-1, 3-benzoxazole-5-carboxylates and 2-substitutedaryl-1, 3-benzoxazole-5-carbohydrazides. The newly synthesized compounds were characterized on the basis of spectral (FT-IR, 1H-NMR, MS) and elemental analysis. All these compounds were screened for anticonvulsant activity using Maximal Electroshock (MES) and subcutaneous pentylenetetrazole (scPTZ) method. Anticonvulsant activity was shown by majority of the synthesized compounds when given i.p. to mice. Among the tested compounds 4e, 4j and 4o were considered to have potent anticonvulsant activity comparable to that of standard drugs Phenytoin and Carbamazepine. Compounds 4e, 4g, 4h, 4i, 4k and 4m passed the rota rod test successfully without any sign of neurological deficit.